Conceptualizing Human Rights Remarks on the ‘Genus’ and Distinguishing Features of Human Rights - Szerletics, Antal (The Age of Human Rights Journal, 2022)
The paper examines the conceptual issues of human rights using the framework of the genus proximum – differentia specifica definitional technique. My aim is not to come up with a definition for human rights, but rather to identify their genus that can, as a starting point, serve the purposes of constructing a more elaborate theory. As an unsurprising, but not at all obvious suggestion, it is argued that the closest conceptual category to human rights is the category of rights, understood in a wide but still Hohfeldian sense of the word. Subsequently, the paper examines five potential ‘distinguishing features’ that can, either separately or in combination with each other, set apart human rights from other rights.